2020
DOI: 10.1111/jan.14290
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐individual variability in sleep is related to glycaemic control in adults with type 2 diabetes

Abstract: Aims To examine whether there were significant differences in sleep during weekdays/weekends and whether the intra‐individual variability in sleep was related to glycaemic control in patients with type 2 diabetes. Design Correlational, longitudinal design. Methods Data were collected between February 2017–January 2018. In all, 56 adults with type 2 diabetes were included (60.7 years, 55.4% female). Sleep was measured using the Consensus Sleep Diary over 8 days. Intra‐individual variability of sleep was calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…In a study by Chontong et al 10 , a difference in sleep regularity of ≈20 minutes in adults with T1D was associated with ≈0.6% difference in A1C. Zhu et al 46 also reported that variability in sleep timing was a significant predictor of A1C in adults with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 95%
“…In a study by Chontong et al 10 , a difference in sleep regularity of ≈20 minutes in adults with T1D was associated with ≈0.6% difference in A1C. Zhu et al 46 also reported that variability in sleep timing was a significant predictor of A1C in adults with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 95%
“…The study further suggested that, among different objective sleep variables including sleep duration and sleep efficiency, the variability of sleep duration between nights was most strongly correlated with HbA1c. Another recent study using an 8‐day sleep diary to record sleep variables also reported significant associations between sleep duration variability/sleep midpoint variability and HbA1c among 56 Chinese T2D patients 28 . The mechanism that links variability in sleep duration and midpoint with glycaemic control remains largely obscure.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study using an 8‐day sleep diary to record sleep variables also reported significant associations between sleep duration variability/sleep midpoint variability and HbA1c among 56 Chinese T2D patients. 28 The mechanism that links variability in sleep duration and midpoint with glycaemic control remains largely obscure. Noticeably, daily intraindividual variability of sleep has been found to be more pronounced among individuals with insomnia symptoms, poor subjective sleep quality, and late chronotype.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in patients with type 1 diabetes (T1D) suggest that higher sleep duration and midpoint time variability are associated with poorer glycemic control after adjusting for covariates such as neurological symptoms, risk of sleep apnea, and self-reported poor sleep quality (34). In patients with type 2 diabetes (T2D), higher variability in self-reported and actigraphymeasured sleep duration is associated with higher HbA1c values (35,36).…”
Section: Diabetesmentioning
confidence: 99%